Who Turned the Filet Mignon into Chopped Meat? - Fred Danzig (Journal of Applied Communications, 1970)
Being enmeshed in the New York rat race—or guinea pig race, since we seem to be a laboratory of sorts, undergoing experiments in problem-solving—I find it easy to tune in to the surging crises that envelop us and threaten, even, to destroy us.